Study on China’s Electronic Information Industrial Agglomeration and Regional Industrial Competitiveness - Xuan Zhaohui; Wu Aizhi; Lv Yongbo (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Spatial agglomeration and industrial competitiveness are currently two key issues in the study of China’s electronic information industrial development. Based on the data for 1995 - 2010, this paper establishes the indicator system to evaluate the competitiveness of regional electronic information industry. In this paper, location Gini coefficient and the indicator of concentration rate are applied to analyze the characteristics and historical evolution of China’s electronic information industrial agglomeration, while benchmarking analysis is also applied to evaluate the competitiveness of provincial regional electronic information industry. The correlation between industrial agglomeration and industrial competitiveness is analyzed in this study. There is a significant positive correlation between them at present. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2854